Clinicopathological, Treatment and Event-Free Survival Characteristics in a Moroccan Population of Triple-Negative Breast Cancer - Fatima Zahra Mouh; Meriem Slaoui; Rachid Razine; Mohammed EL Mzibri; Mariam Amrani (Breast Cancer: Basic and Clinical Research, 2020)
Introduction: Triple-negative breast cancer (TNBC) is a group of breast carcinoma characterized by the lack of expression of estrogen and progesterone hormone receptors (ER, PgR) and HER2. This form is also characterized by its aggressiveness, a low survival rate, and the absence of targeted therapies. This study was planned to evaluate the clinical features, treatment, and prognosis characteristics of TNBC in a population of Moroccan patients. Methods: In this retrospective study, a total of 905 patients diagnosed with breast cancer at the National Institute of Oncology in Rabat, Morocco, have been included. Based on molecular subtype, patients were divided into 2 categories: TNBC and non-TNBC patients. Data were recorded from patients’ medical files and analyzed using SPSS 13.0 software (IBM). Results: Overall, 17% of the patients had TNBC. At diagnosis, the median age of TNBC cases was 47 years, with extreme ages of 40 and 55 years. The median follow-up time was 30 months (10-53 months) and the 3-year survival rate was 76%. No significant difference was observed among the patients in terms of age at diagnosis, age at menarche, age at the time of first birth, nulliparity, oral contraception, and family history of breast cancer. Menopausal status and the number of pregnancy were significantly higher in the non-TNBC group. The percentage of grade 3 (G3) tumors was higher in the TNBC group ( P  < .001). Using neoadjuvant, adjuvant chemotherapy and radiotherapy, a net benefit in the event-free survival was registered for the 2 groups. Conclusions: This retrospective study was very informative and showed that women with TNBC had a less favorable prognosis than non-TNBC cases. Clinical data demonstrated that risk factors including age, premenopausal status, parity, hormonal contraceptive use, advanced disease, and a high histologic grade were independently associated with TNBC. However, large tumors and high Scarff-Bloom and Richardson grade prevail in TNBC cases with a higher incidence of lymph node metastases.